Cystine reductase in the dimorphic fungus Histoplasma capsulatum. - Maresca, B (1978)
Organo-sulfur compounds favor the transition of mycelia of Histoplasma capsulatum to the yeast form (6, 8). Investigation of the role of cystine in the transition revealed that the two phases concentrated this amino acid at comparable rates and that mutants defective in the uptake of cystine were still able to undergo the transition normally. Uptake of cystine is therefore probably not a requirement for transition to or maintenance of the yeast phase. Both phases contained a reduced nicotinamide adenine dinucleotide phosphate-dependent glutathione reductase; but a reduced nicotinamide adenine dinucleotide-dependent cystine reductase was detectable only in the yeast phase. The cystine reductase appeared early in the transition of mycelium to yeast. Treatment of mycelia with p-chloromercuriphenylsulfonic acid, which prevented the transition to yeast, had no effect on cystine uptake but strongly inhibited the cystine reductase. These results suggest that cystine reductase may provide reduced sulfhydryl groups involved in the transition of mycelium to yeast.